Systematic studies on the kinetic process of 20(S)-protopanaxadiol in rats and dogs: absorption, distribution, metabolism and excretion - Li, Pengfei; Zhang, Min; Chen, Meng; Liu, Guangxu; Meng, Linghui; Zhang, Dan (Frontiers in Pharmacology, 2024)
Background and Objective: Ginseng has been regarded as a precious medicinal herb with miraculous effects in Eastern culture. The primary chemical constituents of ginseng are saponins, and the physiological activities of ginsenosides determine their edible and medicinal value. The aim of this study is to comprehensively and systematically investigate the kinetic processes of 20 (S) -protopanaxadiol (PPD) in rats and dogs, in order to promote the rational combination of ginseng as a drug and dietary ingredient. Methods: PPD was administered, and drug concentration in different biological samples were detected by liquid chromatography tandem mass spectrometry (LC/MS/MS) and radioactive tracer methods. Pharmacokinetic parameters such as absorption, bioavailability, tissue distribution, plasma protein binding rate, excretion 2 / 20 rate, and cumulative excretion were calculated, along with inference of major metabolites.Results: This study systematically investigated the absorption, distribution, metabolism, excretion (ADME) of PPD in rats and dogs for the first time. The bioavailabilities of PPD were relatively low, with oral absorption nearly complete, and the majority underwent first-pass metabolism. PPD had a high plasma protein binding rate and was relatively evenly distributed in the body. Following oral administration, PPD underwent extensive metabolism, potentially involving one structural transformation and three hydroxylation reactions. The metabolites were primarily excreted through feces and urine, indicating the presence of enterohepatic circulation. The pharmacokinetic processes of PPD following intravenous administration aligned well with a three-compartment model. In contrast, after gastric administration, it fitted better with a two-compartment model, conforming to linear pharmacokinetics and proportional elimination. There were evident interspecies differences between rats and dogs regarding PPD, but individual variations of this drug were minimal within the same species.Conclusion: This study systematically studied the kinetic process of PPD in rats and also investigated the kinetic characteristics of PPD in dogs for the first time. These findings lay the foundation for further research on the dietary nutrition and pharmacological effects of PPD.